2009 IEEE International Conference on Data Mining Workshops 2009
DOI: 10.1109/icdmw.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Differentially Private Random Decision Tree Classifier

Abstract: Abstract-In this paper, we study the problem of constructing private classifiers using decision trees, within the framework of differential privacy. We first construct privacy-preserving ID3 decision trees using differentially private sum queries. Our experiments show that for many data sets a reasonable privacy guarantee can only be obtained via this method at a steep cost of accuracy in predictions.We then present a differentially private decision tree ensemble algorithm using the random decision tree approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 14 publications
(18 reference statements)
1
133
0
Order By: Relevance
“…With the success of differentially private algorithms for tabular data [16,8,1,25,26,13,18,5], there has been interest in developing differentially private mechanisms for other domains, such as social networks [12]. For social networks, examples include [17,27,30].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With the success of differentially private algorithms for tabular data [16,8,1,25,26,13,18,5], there has been interest in developing differentially private mechanisms for other domains, such as social networks [12]. For social networks, examples include [17,27,30].…”
Section: Related Workmentioning
confidence: 99%
“…Query answering algorithms that satisfy differential privacy must produce noisy query answers such that the distribution of query answers changes very little with the addition, deletion, or modification of any tuple. Recent work has shown that the resulting query answers can enable very accurate privacy-preserving statistical analyses of sensitive datasets [25,13,5,18]. There are two flavors of differential privacy, which we call unbounded and bounded.…”
Section: Introductionmentioning
confidence: 99%
“…The merit of building a random tree is the efficiency of training and minimal memory requirements. To create a random decision tree, Random Tree algorithm uses only one pass over the data [17,19].…”
Section: Random Treementioning
confidence: 99%
“…Although it is possible to extend binary classification algorithms to multi-class using techniques like one-vsall, it is much more expensive to do so as compared to a naturally multi-class classification algorithm. Jagannathan, et al [11] present a differentially private random decision tree learning algorithm which can be applied to multi-class classification. Their approach involves perturbing leaf nodes using the sensitivity method, and they do not provide theoretical analysis of excess risk of the perturbed classifier.…”
Section: Related Workmentioning
confidence: 99%